RESTRICTING IMMIGRANTS, COLONIAL INHERITANCE AND POLITICAL INTERESTS: AUSTRALIAâ€™S CITIZENSHIP TEST UNDER THE HOWARD GOVERNMENT - Iqbal, Asep (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
In 2006, Australia under the Howard government proposed a citizenship test aimed at restricting immigration and toughening citizenship requirements. To understand this proposed citizenship, this essay attempts to analyze the basic ideas of the test by explaining its possible relationship with Australiaâ€™s past history and Australiaâ€™s dependence on the â€˜superpowerâ€™ countries in the issue. It explains that the proposed citizenship test reflected John Howardâ€™s political brands and manifested his wonderful skills in understanding and exploiting the living fears of â€˜the otherâ€™ among Australian people for political gain in his second term. The huge support for the proposed citizenship test indicated that the fear of â€˜the otherâ€™ and â€˜potential enemiesâ€™ was still evident among Australian. It also served as evidence that multiculturalism was under threat because people considered it as a policy that undermines dominant culture.Â  The article argues that Australiaâ€™s colonial past still plays a role in peopleâ€™s attitudes and government policies. â€œThe chains of colonial inheritanceâ€ has not disappeared in contemporary Australia.Â  Â